HAK DESAIN TATA LETAK SIRKUIT TERPADU PADA IMPLEMENTASI ALGORITMA ENKRIPSI BC3 DI INDONESIA: Integrated Circuit Layout Design Rights In The Implementation Of The Bc3 Encryption Algorithm In Indonesia - Vania Agata; Rr. Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2024)
Integrated circuit layout design (DTLST) is one of the relatively new forms of intellectual property, especially in the context of Industrial Property Rights. Law No. 32 of 2000 regulates the layout design of integrated circuits. The first DTLST certificate was granted by DJKI Kemenkhumham in 2018 with certificate number IDL000000001 to Dr. Eng. Sarwono Sutikno and team. The problem formulation in this article is how the legal protection process of Layout Design of BC3 Encryption Algorithm Implementation on Hardware with DTLST Number IDL000000001 according to Law No. 32 of 2000 concerning DTLST and whether that design has qualified as an Integrated Circuit Layout Design. The research uses normative legal research methods, with secondary and primary data. Based on the results of the study, the Layout Design of BC3 Encryption Algorithm Implementation on Hardware has protection for 10 years since October 30th, 2018, where the protection is obtained from the date of acceptance because no commercial exploitation is carried out. The conclusion is that The Layout Design of BC3 Encryption Algorithm Implementation on Hardware is a work that has passed the checking process by DJKI, where this design has passed and meets the originality requirements.